The future of domestic capital markets in developing countries - Litan, Robert E., 1950-; Pomerleano, Michael; Sundararajan, Vasudevan (Washington, D.C. : Brookings Institution Press, 2003)
This volume brings together financial sector experts and leaders from around the world to provide practical guidance on strategies such as nuturing issuers, improving rules and institutions, addressing regulatory challenges and sequencing reforms.
9. Managing Risks in Financial Market Development: The Role of SequencingPanel Summary: Does Integrated Supervision Work in Emerging Markets?; 10. Changing Market Structures, Demutualization, and the Future of Securities Trading; 11. Corporate Governance Issues and Returns in Emerging Markets; 12. Capital Structures and Control Rights: Patterns, Trade-offs, and Policy Implications; 13. Identifying Vulnerabilities, Promoting Fin.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Capital market -- Developing countries; Capital market -- Government policy -- Developing countries; Capital market -- Law and legislation -- Developing countries; BUSINESS & ECONOMICS -- Finance; BUSINESS & ECONOMICS -- Development -- Economic Development; Capital market; Capital market -- Government policy; Capital market -- Law and legislation; Developing countries